Strategies for enhancing the semi-dry and dry anaerobic biometanization of swine manure - Silva, Amanda de Sousa e (2023)
Pig farming is one of the most important agricultural activities in the world, with Brazil being the fourth largest producer and exporter of pigs. However, this activity generates large volumes of organic waste, such as swine manure (DS), with a high load of organic matter, nitrogen, phosphorus, heavy metals, pathogens, and antibiotics, which causes several environmental problems. In addition, a climate and energy crisis requires the search for alternative energy sources. In this context, anaerobic digestion (AD) emerges as a sustainable alternative to convert waste into energy (biogas and methane). Therefore, this work sought to evaluate strategies to enhance the anaerobic biometanization of swine manure, such as thermos-alkaline pretreatment (3% NaOH at 121 ∫C for 30 min), total solids content – TS (10 and 15% TS), substrate/inoculum (SI) ratio (1, 3 and 5 g.VSsubstrate / g.VSinoculum) and addition of granular activated carbon - GAC (10, 20 and 30 g/L) as conductive material, applying kinetic modeling analysis to understand the influence of the evaluated parameters better and generate important kinetic coefficients for optimization and process scaling, and molecular biology tools for a better comprehension of the different microbial population involved and ecology dynamics changes. For this, Biochemical Methane Potential (BMP) experiments were conducted in batch mode under mesophilic temperature and orbital shaking at 150 rpm for 90 days. In the first phase of the research, the pretreatment increased the biodegradability of the manure, thus increasing the accumulated methane yield for the two conditions tested (10% TS: from 30 to 205 mL CH4/gVS and 15% TS: from 0 to 136 mL CH4/gVS). On the other hand, increasing the SI ratio for the pretreated manure proved to be viable only in the semi-dry condition (205, 268, and 187 mL CH4/gVS for SI 1, 3, and 5, respectively), as in the dry condition there was only significant methane production in SI 1 (136 mL CH4/gVS). In the second phase, the addition of 20 g GAC/L promoted an increase in methane yield from 3 to 154 and 155 mL CH4/gVS with raw and pretreated manure, respectively, in semi-dry condition (10% TS). Therefore, there was no significant difference when carrying out pretreatment. Regarding the study of GAC dosage for pretreated manure in semi-dry AD, the addition of 10 g GAC/L yielded 190 mL CH4/gVS, a value 21% higher than with 20 and 30 g GAC/L, although the kinetics were more favorable for the concentration of 20 g/L, according to the Modified Gompertz model, which best described the process. In dry AD (15% TS), the optimal GAC concentration was 30 g/L (157 mL CH4/gVS).